2011
DOI: 10.1292/jvms.10-0433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclophosphamide on the Kaolin Consumption (Pica Behavior) in Five Strains of Adult Male Rats

Abstract: ABSTRACT. It is known that pica, the consumption of non-nutritive substances such as kaolin, can be induced by administration of toxins or emetic agents in rats. In the present study, we examined the effects of intraperitoneal (i.p.) administration of cyclophosphamide on pica behavior and on the concentration of 5-hydroxyindoleacetic acids (5HIAA) in cerebrospinal fluid (CSF) in the following five strains of adult male rats: Sprague Dawley (SD), Wistar, Fischer 344 (F344), Wistar-Imamichi (WI) and Long Evans (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…Aberrant pica behavior (kaolin clay intake) has been regarded as a marker of nausea in rats (Andrews & Horn, 2006) that cannot vomit because of anatomical and/or neural reasons (Horn et al, 2013). Pica behavior is generated by a variety of nausea-inducing treatments, including irradiation (e.g., , motion sickness (e.g., Mitchell, Laycock, & Stephens, 1977), and administration of emetic drugs such as lithium chloride (LiCl; e.g., Mitchell et al, 1976), cyclophosphamide (e.g., Tohei, Kojima, Ikeda, Hokao, & Shinoda, 2011), cisplatin (e.g., Takeda, Hasegawa, Morita, & Matsunaga, 1993), ritonavir (e.g., Aung et al, 2005), morphine (e.g., Aung, Mehendale, Xie, Moss, & Yuan, 2004), and apomorphine (e.g., Takeda et al, 1995), among others (see the introduction of Nakajima, 2016a, for a more detailed review).…”
mentioning
confidence: 99%
“…Aberrant pica behavior (kaolin clay intake) has been regarded as a marker of nausea in rats (Andrews & Horn, 2006) that cannot vomit because of anatomical and/or neural reasons (Horn et al, 2013). Pica behavior is generated by a variety of nausea-inducing treatments, including irradiation (e.g., , motion sickness (e.g., Mitchell, Laycock, & Stephens, 1977), and administration of emetic drugs such as lithium chloride (LiCl; e.g., Mitchell et al, 1976), cyclophosphamide (e.g., Tohei, Kojima, Ikeda, Hokao, & Shinoda, 2011), cisplatin (e.g., Takeda, Hasegawa, Morita, & Matsunaga, 1993), ritonavir (e.g., Aung et al, 2005), morphine (e.g., Aung, Mehendale, Xie, Moss, & Yuan, 2004), and apomorphine (e.g., Takeda et al, 1995), among others (see the introduction of Nakajima, 2016a, for a more detailed review).…”
mentioning
confidence: 99%
“…A similar increase in plasma glucocorticoids levels was also reported in dogs and rats: Kenward et al ( 2014 ) reported that CDDP administration to dogs increased plasma Cor levels simultaneously with the vomiting. Similarly, Tohei et al ( 2011 ) reported that the administration of cyclophosphamide, another emetic agent, induced pica, and a significant increase in plasma corticosterone levels in rats. The blood levels of corticoids are the most popular physiological indicator of the stress.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, Tohei et al (2011) reported that the administration of cyclophosphamide, another emetic agent, induced pica, and a significant increase in plasma corticosterone levels in rats. The blood levels of corticoids are the most popular physiological indicator of the stress.…”
Section: Discussionmentioning
confidence: 85%
“…Using our system, we could evaluate whether each medicine causes mild pellagra or not. Furthermore, previous studies indicated that mice with cisplatin-related pica were improved by antiemetic agents such as ondansetron, which were used in a clinical site (30). Because this INH-related pica was significantly attenuated after niacin treatment only in rodents, it needs further investigations in clinical research.…”
Section: Discussionmentioning
confidence: 99%